(untitled) (Semiárida, 2018)
The area of wheat cropping in La Pampa province is included in the Region V South of Argentina for production of that cereal, where water and nitrogen low availabilities are the main limiting factors for wheat grain yield. The present work was aimed at analyzing grain yield and changes in grain protein composition of four genotypes of Triticum aestivum L. subjected to different availability levels of water and nitrogen. The assay was performed in pots under greenhouse condition and utilizing wheat cultivars ACA 315, Baguette Premium 11, Klein Proteo and DM Cronox. At the start of flowering half of the pots were fertilized with 100 kg N ha-1 and, until grain harvest, half of the pots were kept at 50 and the other half at 100% field capacity. Grain yield components, greenness index, grain protein concentration, grain nitrogen content and gliadins and glutenins concentration in flour were the variables determined in the assay. DM Cronox was the cultivar that expressed the highest grain yield. Under conditions of limiting water availability, the gluteninrich fraction increased and that of gliadins decreased in two of the genotypes, whereas addition of nitrogen led to an increase only in the glutenin content. Concentrations of protein fractions are associated to grain nitrogen content, mainly for gliadins. The change in wheat grain protein fractions upon variation of water and nitrogen availabilities depends on the genotype environment relationship. DOI: http://dx.doi.org/10.19137/semiarida.2017(02).3750